Cinema e cultura midiática: a pequena loja de suicídios - representações em torno do mal-estar na modernidade líquida - Sarques, Brenno Alves Pereira (2018)
This study seeks to analyse the association between the animation film and the malaise in the liquid modern society, an historical period formed by changes in communications, interpersonal relationships, people and nation identities, in global integration, in the presence of international capital and its interference in local and national issues, and its consequences on the human individuality and its social behavior. The cinema, as a representation of reality, is not oblivious to this phenomenon of modernity. So, from the film analysis of the movie The Suicide Shop, this research seeks to draw which elements of this malaise are evident in the movie and how the animation film plays these questions. From this point on, it will be possible to see what is the contribution this movie genre gives to the debate about the malaise in the liquid modern society. The emplyed methodology is the film analysis, supported by a deep theorical research on concepts of disenchantment, liquid modernity, identity and animation movies. The result of it was an analysis which revealed a storng relationship from The Suicide Shop approaches on suicide and the malaise in the liquid modern society to the sociological concepts of these issues. The animation cinema was able to represent the occidental culture hit by the disenchantment of the liquid modern society in such a strong way to set itself as a great communication and identification link between art and society.